Solid state battery

JP7632177B2Active Publication Date: 2025-02-19TOYOTA JIDOSHA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021136926
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-25
Publication Date
2025-02-19
Estimated Expiration
2041-08-25

Smart Images

  • Figure 0007632177000003
    Figure 0007632177000003
  • Figure 0007632177000001
    Figure 0007632177000001
  • Figure 0007632177000002
    Figure 0007632177000002
Patent Text Reader

Abstract

To provide a solid-state battery with low battery resistance.SOLUTION: The solid-state battery includes an electrode layer including electrode active material and solid electrolyte. An average particle diameter D50 of particles of the solid electrolyte is less than 0.7 μm. The average particle diameter D50 of the particles of the electrode active material is 0.47 μm or more and 0.63 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to solid-state batteries. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway. Moreover, solid-state batteries have attracted attention because they use a solid electrolyte as the electrolyte between the positive electrode and the negative electrode, instead of an electrolytic solution containing an organic solvent.

[0003] Patent Document 1 discloses sulfide-based solid electrolyte fine particles containing elemental sulfur, elemental lithium, and elemental phosphorus as main components and having an average particle size of 0.1 to 10 μm.

[0004] Patent Document 2 discloses that the first garnet-type solid electrolyte powder has an average particle size of 1 to 13 μm, the coefficient of variation, expressed as standard deviation (μm) / average diameter (μm)×100, is less than 20%, and the second garnet-type solid electrolyte powder has an average particle size of 0.1 to 1.5 μm. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-004459 A [Patent Document 2] JP 2020-035678 A Summary of the Invention [Problem to be solved by the invention]

[0006] When an active material having a relatively small average particle size is used, the dispersibility with a solid electrolyte having a relatively large average particle size is poor, and the battery resistance of the solid-state battery increases.

[0007] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a solid-state battery having low battery resistance. [Means for solving the problem]

[0008] The solid-state battery of the present disclosure includes an electrode layer including an electrode active material and a solid electrolyte, The solid electrolyte particles have an average particle size D50 of less than 0.7 μm; The average particle size D50 of the particles of the electrode active material is characterized by being 0.47 μm or more and 0.63 μm or less. Effect of the Invention

[0009] The present disclosure provides an electrode layer in which particles of an electrode active material are combined with solid electrolyte particles having an average particle size close to the average particle size of the particles of the electrode active material, thereby improving the dispersibility of the electrode layer and reducing the battery resistance of the solid-state battery. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The solid-state battery of the present disclosure includes an electrode layer including an electrode active material and a solid electrolyte, The solid electrolyte particles have an average particle size D50 of less than 0.7 μm; The average particle size D50 of the particles of the electrode active material is characterized by being 0.47 μm or more and 0.63 μm or less.

[0012] FIG. 1 is a schematic cross-sectional view showing an example of a solid-state battery according to the present disclosure. As shown in FIG. 1, the solid-state battery 100 includes an anode current collector 11, an anode layer 12, a solid electrolyte layer 13, a cathode layer 14, and a cathode current collector 15, in this order.

[0013] The solid-state battery of the present disclosure includes an electrode layer. The electrode layer of the present disclosure contains an electrode active material and a solid electrolyte, and optionally contains a conductive material, a binder, and the like. The electrode layer is a positive electrode layer or a negative electrode layer. Two electrode layers containing different types of electrode active materials may be prepared, one of which may be used as a positive electrode layer and the other as a negative electrode layer.

[0014] As the electrode active material, any material that can be used as an active material for a solid-state battery can be used, and materials similar to those exemplified as the positive electrode active material and the negative electrode active material described later can be used. The average particle diameter D50 of the electrode active material particles is 0.47 μm or more and 0.63 μm or less. The specific surface area of ​​the electrode active material particles is 34 m 2 / g or more 62m 2 / g or less.

[0015] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The average particle size D50 of the solid electrolyte particles in the electrode layer is less than 0.7 μm. The average particle size D50 of the solid electrolyte particles in the electrode layer may be 0.1 μm or more, 0.3 μm or more, 0.69 μm or less, or 0.5 μm or less. The specific surface area of ​​the solid electrolyte particles in the electrode layer is 18.2 m 2 / g or more 29.8m 2 / g or less.

[0016] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.

[0017] Examples of the conductive material and binder include the same materials as those exemplified in the positive electrode layer.

[0018] The electrode layer may be produced, for example, by the following method: Particles of the electrode active material, particles of the solid electrolyte, a conductive material, and a binder are mixed with an organic solvent (dispersion medium) such as N-methylpyrrolidone to form a slurry (or a paste). The slurry (or paste) may be applied onto a current collector and dried to form an electrode layer on the current collector.

[0019] The solid-state battery of the present disclosure may include a positive electrode including a positive electrode layer, a solid electrolyte layer, and a negative electrode including a negative electrode layer. At least one of the positive electrode layer and the negative electrode layer may be the electrode layer used in the present disclosure.

[0020] [Positive electrode] The positive electrode includes a positive electrode layer and, optionally, a positive electrode current collector.

[0021] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain, as optional components, a solid electrolyte, a conductive material, a binder, etc. When the positive electrode layer contains a positive electrode active material and a solid electrolyte, the positive electrode layer may be the electrode layer of the present disclosure.

[0022] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for a solid-state battery can be used. When the solid-state battery is a solid-state lithium secondary battery, the positive electrode active material can be, for example, metallic lithium (Li), a lithium alloy, LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi x Co 1-x O2(0 <x<1)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3Examples of the Li-Mn spinel substituted with a different element include LiO2, LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, and Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with a different element is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 O4, etc. Lithium titanate is, for example, Li4Ti5O 12 The lithium metal phosphates are, for example, LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. The transition metal oxides are, for example, V2O5, and MoO3. The lithium storage intermetallic compounds are, for example, Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of Si alloys include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. Meanwhile, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coverage of the coating layer on the surface of the positive electrode active material is, for example, 70% or more, and may be 90% or more.

[0023] The solid electrolyte may be the same as those exemplified in the solid electrolyte layer. In addition, the solid electrolyte may have the average particle size and specific surface area shown in the electrode layer. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.

[0024] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.

[0025] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.

[0026] The thickness of the positive electrode layer is not particularly limited.

[0027] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a positive electrode layer slurry, and the positive electrode layer slurry is applied onto one side of a support such as a positive electrode current collector and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the positive electrode layer slurry onto one surface of a support such as a positive electrode current collector is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.

[0028] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 2000 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.

[0029] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for solid-state batteries. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0030] [Negative electrode] The negative electrode includes a negative electrode layer and, optionally, a negative electrode current collector.

[0031] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material, and optionally contains a solid electrolyte, a conductive material, a binder, etc. When the negative electrode layer contains a negative electrode active material and a solid electrolyte, the negative electrode layer may be the electrode layer of the present disclosure. The negative electrode active materials include graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, soft carbon, lithium alone, lithium alloy, Si alone, Si alloy, and Li4Ti5O 12 As the lithium alloy and the Si alloy, the same ones as those exemplified in the positive electrode active material can be used. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape, a plate shape, etc. When the negative electrode active material is particulate, the negative electrode active material may be primary particles or secondary particles. The shape of the negative electrode active material is not particularly limited, and examples thereof include a particulate shape and a plate shape. The conductive material and binder used in the negative electrode layer may be the same as those exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as those exemplified in the solid electrolyte layer. In addition, the solid electrolyte used in the negative electrode layer may have the average particle size and specific surface area of ​​the solid electrolyte particles shown in the electrode layer. The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm. The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 90% by mass.

[0032] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, and examples thereof include SUS, copper, and nickel. Examples of the form of the negative electrode current collector include foil and plate. The planar shape of the negative electrode current collector is not particularly limited, and examples thereof include a circle, an ellipse, a rectangle, and any polygonal shape. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0033] [Solid electrolyte layer] The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, any known solid electrolyte that can be used in solid-state batteries can be appropriately used, and examples of such solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes. Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiX-Li2S-SiS2, LiX-Li2S-P2S5, LiX-Li2O-Li2S-P2S5, LiX-Li2S-P2O5, LiX-Li3PO4-P2S5, and Li3PS4. The above description of "Li2S-P2S5" means a material made using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. In addition, "X" in the above LiX indicates a halogen element. The raw material composition containing LiX may contain one type or two or more types of LiX. When two or more types of LiX are contained, the mixing ratio of the two or more types is not particularly limited. The molar ratio of each element in the sulfide-based solid electrolyte can be controlled by adjusting the content of each element in the raw material. The molar ratio and composition of each element in the sulfide-based solid electrolyte can be measured, for example, by ICP emission spectrometry.

[0034] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.

[0035] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.

[0036] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.

[0037] Examples of oxide-based solid electrolytes include substances having a garnet-type crystal structure containing, for example, Li, La, A (A is at least one of Zr, Nb, Ta, and Al), and O. 3+x PO 4-x N x (1≦x≦3), etc.

[0038] The solid electrolyte may be in the form of particles from the viewpoint of ease of handling.

[0039] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, may be in the range of 60% by mass or more and 100% by mass or less, may be in the range of 70% by mass or more and 100% by mass or less, or may be 100% by mass.

[0040] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.

[0041] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method for forming the solid electrolyte layer includes a method of pressing a powder of a solid electrolyte material containing a solid electrolyte, etc. When pressing the powder of the solid electrolyte material, a press pressure of about 1 MPa or more and 2000 MPa or less is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.

[0042] The solid-state battery may include an exterior body that houses a laminate including a positive electrode current collector, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector in this order, and a restraining member, as necessary. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin. The restraining member may be any known member usable as a restraining member for a solid-state battery, as long as it can apply a restraining pressure in the stacking direction to the laminate. For example, a restraining member having plate-shaped parts that sandwich both surfaces of the laminate, a rod-shaped part that connects the two plate-shaped parts, and an adjustment part that is connected to the rod-shaped part and adjusts the restraining pressure by a screw structure or the like can be used. The adjustment part can apply a desired restraining pressure to the laminate. The restraining pressure is not particularly limited, but may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. By increasing the restraining pressure, there is an advantage that it is easier to improve the contact between the layers. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. If the restraining pressure is too high, the restraining member is required to have high rigidity, and the restraining member may become large.

[0043] The solid-state battery may have only one of the laminates described above, or may be formed by stacking a plurality of the laminates. The solid-state battery may be a primary battery or a secondary battery, but may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as an in-vehicle battery. The solid-state battery may be a solid-state lithium secondary battery or a solid-state lithium ion secondary battery. Examples of the shape of the solid-state battery include a coin type, a laminate type, a cylindrical type, and a square type. In the present disclosure, a solid-state battery may be any battery that uses a solid electrolyte instead of an electrolytic solution containing an organic solvent as the electrolyte of an electrolyte layer interposed between a positive electrode and a negative electrode, and may be an all-solid-state battery in which the positive electrode, the negative electrode, and the electrolyte layer are all made of solid materials.

[0044] In the method for producing the solid-state battery of the present disclosure, for example, first, a solid electrolyte layer is formed by pressure-molding a powder of a solid electrolyte material. Then, a positive electrode layer is obtained by pressure-molding a powder of a positive electrode material including a positive electrode active material onto one surface of the solid electrolyte layer. Then, a negative electrode layer is obtained by pressure-molding a powder of the negative electrode material onto one surface of a negative electrode current collector. A negative electrode current collector-negative electrode layer laminate is attached to the surface of the solid electrolyte layer opposite to the surface on which the positive electrode layer is formed, so that the negative electrode layer is in contact with the solid electrolyte layer. Then, a positive electrode current collector is attached to the surface of the positive electrode layer opposite to the solid electrolyte layer. This may form the solid-state battery of the present disclosure. In this case, the pressing pressure when the powder of the negative electrode material, the powder of the solid electrolyte material, and the powder of the positive electrode material are press-molded is usually about 1 MPa or more and 2000 MPa or less. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer. EXAMPLES

[0045] Example 1 [Preparation of negative electrode] The following were used: 18.6 g of particles of the negative electrode active material, which is a nanomaterial having the physical properties shown in Table 1; 17.6 g of particles of a sulfide-based solid electrolyte as a solid electrolyte; 2.4 g of a conductive material; SBR as a binder diluted to 5 wt%; and 1.9 g of DIBK (diisobutyl ketone) as a dispersion medium. The sulfide-based solid electrolyte was a material having the physical properties described in Example 1 in Table 1. The solid content of the paste was adjusted to 31 wt%. A Filmix kneading device was used, and the peripheral speed was adjusted to a range of 5 m / s to 30 m / s, and these materials were kneaded to prepare a negative electrode layer paste. A high-shear type PC wheel was used for the Filmix. The obtained negative electrode layer paste was applied onto a negative electrode current collector by a blade coating method using an applicator and dried at 100°C for 30 minutes to obtain a negative electrode having a negative electrode layer on the negative electrode current collector. The measurement results of the ionic conductivity of the solid electrolyte used to prepare the negative electrode are shown in Table 1. A predetermined positive electrode for evaluation and a predetermined solid electrolyte layer for evaluation were prepared, and a solid battery having a positive electrode, a solid electrolyte layer, and a negative electrode was obtained. [Battery characteristic evaluation] The solid-state battery was subjected to 4 cycles of CCCV charge and discharge at 0.1C from an upper limit voltage of 4.05V to a lower limit voltage of 2.5V. After that, the solid-state battery was set to a discharge SOC of 20%, and the battery resistance of the solid-state battery was measured. The DC resistance was measured at 1.7C. The design capacity of the solid-state battery was 0.4Ah. The results are shown in Table 1.

[0046] (Examples 2 to 3) A negative electrode layer paste was prepared in the same manner as in Example 1, except that a sulfide-based solid electrolyte was used as the negative electrode active material and solid electrolyte having the physical properties shown in Table 1, and a solid battery was obtained. The battery characteristics of the obtained solid battery were evaluated in the same manner as in Example 1. The measurement results of the ionic conductivity of the solid electrolyte used to prepare the negative electrode and the measurement results of the battery resistance of the solid battery are shown in Table 1.

[0047] (Examples 4 to 6) A negative electrode layer paste was prepared in the same manner as in Example 1, except that a sulfide-based solid electrolyte was used as the negative electrode active material and solid electrolyte having the physical properties shown in Table 1, and the solid content of the paste was adjusted to 28 wt%, to obtain a solid battery. The battery characteristics of the obtained solid battery were evaluated in the same manner as in Example 1. The measurement results of the ionic conductivity of the solid electrolyte used to prepare the negative electrode and the measurement results of the battery resistance of the solid battery are shown in Table 1.

[0048] (Comparative Examples 1 to 3) A negative electrode layer paste was prepared in the same manner as in Example 1, except that a sulfide-based solid electrolyte was used as the negative electrode active material and solid electrolyte having the physical properties shown in Table 2, and the solid content of the paste was adjusted to 39 wt%, to obtain a solid battery. The battery characteristics of the obtained solid battery were evaluated in the same manner as in Example 1. The measurement results of the ionic conductivity of the solid electrolyte used to prepare the negative electrode and the measurement results of the battery resistance of the solid battery are shown in Table 2.

[0049] (Comparative Examples 4 to 6) A negative electrode layer paste was prepared in the same manner as in Example 1, except that a sulfide-based solid electrolyte was used as the negative electrode active material and solid electrolyte having the physical properties shown in Table 2, and the solid content of the paste was adjusted to 35 wt%, to obtain a solid battery. The battery characteristics of the obtained solid battery were evaluated in the same manner as in Example 1. The measurement results of the ionic conductivity of the solid electrolyte used to prepare the negative electrode and the measurement results of the battery resistance of the solid battery are shown in Table 2.

[0050] (Comparative Examples 7 to 9) A negative electrode layer paste was prepared in the same manner as in Example 1, except that a sulfide-based solid electrolyte was used as the negative electrode active material and solid electrolyte having the physical properties shown in Table 2, and the solid content of the paste was adjusted to 31 wt %, to obtain a solid battery. The battery characteristics of the obtained solid battery were evaluated in the same manner as in Example 1. Table 2 shows the measurement results of the ionic conductivity of the solid electrolyte used to prepare the negative electrode and the measurement results of the battery resistance of the solid battery.

[0051] (Comparative Examples 10 to 14) 18.6 g of particles of a conventional negative electrode active material that is not a nano material and has the physical properties shown in Table 2, 17.6 g of particles of a sulfide-based solid electrolyte as a solid electrolyte having the physical properties shown in Table 2, 2.4 g of a conductive material, SBR as a binder diluted to 5 wt%, and 1.9 g of DIBK (diisobutyl ketone) as a dispersion medium were used. The solid content of the paste was adjusted to 38 to 52 wt%. A kneading device was used, and the peripheral speed was adjusted to a range of 5 m / s to 30 m / s, and these materials were kneaded to prepare a negative electrode layer paste. A solid battery was obtained in the same manner as in Example 1 except for this. The battery characteristics of the obtained solid battery were evaluated in the same manner as in Example 1. Table 2 shows the measurement results of the ion conductivity of the solid electrolyte used to prepare the negative electrode and the battery resistance of the solid battery.

[0052] [Table 1]

[0053] [Table 2]

[0054] [Evaluation Results] As shown in Tables 1 to 2, it is understood that the battery resistances of Examples 1 to 6 are lower than those of Comparative Examples 1 to 14. In Comparative Examples 1 to 9, when the D50 of the negative electrode active material particles was relatively small, if the D50 of the solid electrolyte particles was larger than the D50 of the negative electrode active material particles, it is believed that dispersibility was low and battery resistance increased. In Comparative Examples 10 to 12, when the D50 of the negative electrode active material particles is relatively large, even if the D50 of the solid electrolyte particles is approximately the same as that of the negative electrode active material particles, the battery resistance is considered to be large because the D50 of the negative electrode active material particles is relatively large to begin with. In Comparative Examples 13 and 14, when the negative electrode active material particles have a relatively large D50 and the solid electrolyte particles have an even larger D50, it is believed that the battery resistance is large because the negative electrode active material particles have a relatively large D50 to begin with. From the above, it can be seen that when negative electrode active material particles with a relatively small average particle size are used in the negative electrode layer, the dispersibility decreases when conventional solid electrolyte particles with a large average particle size are used, and the battery characteristics also decrease accordingly. On the other hand, it was confirmed that by combining negative electrode active material particles with a relatively small average particle size with solid electrolyte particles whose average particle size is close to that of the negative electrode active material particles, the dispersibility of the negative electrode layer is improved, and the battery characteristics are improved (battery resistance is reduced). It is presumed that the dispersibility is also improved in the positive electrode layer, and the battery characteristics are improved (battery resistance is reduced). [Explanation of symbols]

[0055] 11 Negative electrode current collector 12 Negative electrode layer 13 Solid electrolyte layer 14 Positive electrode layer 15 Positive electrode current collector 100 solid state battery

Claims

1. An electrode layer including an electrode active material and a solid electrolyte, The solid electrolyte particles have an average particle size D50 of 0.3 μm or more and 0.5 μm or less, The average particle size D50 of the particles of the electrode active material is 0.47 μm or more and 0.63 μm or less, The solid electrolyte of the solid battery is a sulfide-based solid electrolyte.

2. The average particle size D50 of the solid electrolyte particles is 0.3 μm, The specific surface area of ​​the solid electrolyte particles is 29.8 m 2 / g; 2. The solid-state battery according to claim 1, wherein the solid electrolyte has an ionic conductivity of 4.3 mS / cm.

3. The electrode active material is a negative electrode active material, The solid-state battery according to claim 2 , wherein the electrode layer is a negative electrode layer.

Citation Information

Patent Citations

  • Solid electrolyte microparticle and its manufacturing method

    JP2008004459A

  • Lithium battery

    JP2009076402A

  • All-solid lithium ion secondary battery and method of manufacturing the same

    JP2012099225A

  • Method for manufacturing all-solid battery, and all-solid battery

    JP2017157305A

  • Solid electrolyte, manufacturing method thereof, and all-solid battery

    JP2019109961A